Parametric Study on Co-Feeding of Municipal Solid Waste and Coal in an IGCC Power Plant with Pre-Combustion Carbon Capture (Chemical Engineering Research Bulletin, 2021)
Municipal solid waste (MSW) is one of the top contributors in greenhouse gas (i.e. methane) emissions - particularly from landfill disposals. However, it could be a remarkable source of renewable energy. In Bangladesh, generation of municipal solid waste is at least 2.7 million tonne per year in the major cities, implying a heavy environmental burden. On the other hand, there are several coal-based power plants are in the pipeline to meet the increasing energy demand in Bangladesh with the potential of significant CO2 emission. To find a remedy to the above situation, a power plant using Integrated Gasification and Combustion Cycle (IGCC) technology with pre-combustion carbon capture is considered in this study. IGCC has the advantage of producing high quality syngas from a wide variety of feed and assists in the capture of CO2 at a lower cost while providing high electric efficiency. The power plant was simulated by commercial simulation packages (Aspen PLUS™ and Aspen HYSYS™) using MSW and bituminous coal (Indonesian) as a combined feed. With a feed rate of 1800 tonne per day, Syngas produced from an entrained flow type gasifier was then treated for CO2 removal using mono-ethanol amine (MEA) solvent after necessary shift in a high temperature shift reactor. About 91% efficiency was achieved in the shift reactor while the CO2 capture efficiency was varied for this study from 30% to 85%. Further parametric variation was studied by varying the moisture content of MSW and MSW to coal feed ratio. Through combustion of the H2 rich syngas in a gas turbine and subsequent steam cycle with reheat resulted in 125 MW of electricity at an efficiency of 28.95% while capturing 50% of the CO2 generated in the process for an MSW to Coal feed ratio of 1:1. With variation in moisture content especially during monsoon season, the plant efficiency could be affected remarkably. On the other hand, it was observed that the energy requirement varied from 6 to 8 MW for every 10% increase in CO2 capture quantity. Overall, by capturing 50% of the generated CO2, it is possible to reduce the emission of a same size ultra-supercritical coal-based power plant from about 700 kg CO2/MWh to about 360 kg of net CO2/MWh incorporating co-feeding and pre-combustion capture in an IGCC power plant.Chemical Engineering Research Bulletin 21(2020) 37-42